Central giant cell granuloma: A case report and review - Krishnaveni Buduru; Sanjay Reddy Podduturi; Dal Singh Vankudoth; Jacob Prakash (Wolters Kluwer Medknow Publications, 2017)
Central giant cell granuloma (CGCG) is a benign intra-osseous lesion of unknown etiology, and occurs in jaws. Clinically and radiographically difference between its nature - aggressive and non-aggressive can be made. It is characterized histologically by cellular fibrous tissue containing multiple foci of hemorrhage, aggregations of multinucleated giant cells, and occasionally, trabeculae of woven bone. Histologically, identical lesions occur in patients with known genetic defects such as cherubism, Noonan syndrome, or neurofibromatosis type I. It has an increased predilection for mandible and females in younger age group. Surgical curettage or resection is the most common therapy in aggressive lesions. The drawback is undesirable damage to the jaw or teeth, tooth germs, and frequent recurrences. Non-aggressive tumors respond well to such treatments. We are presenting a case of an aggressive type of CGCG of mandible in a young patient, who presented with massive swelling associated with loss of teeth in just 6 months duration.